Mitigating adjacent channel interference in vehicular communication systems - Almeida, João Miguel Pereira (2016)
In the last few decades, dedicated wireless channels were specifically allocated to enable the development and implementation of vehicular communication systems. The two main protocol stacks, the WAVE standards proposed by the IEEE in the United States and the ETSI ITS-G5 in Europe, reserved 10 MHz wide channels in the 5.9 GHz spectrum band. Despite the exclusive use of these frequencies for vehicular communication purposes, there are still cross channel interference problems that have been widely reported in the literature. In order to mitigate these issues, this paper presents the design of a two-stage FIR low-pass filter, targeting the integration with a digital baseband receiver chain of a custom vehicular communications platform. The filter was tested, evaluated and optimized, with the simulation results proving the effectiveness of the proposed method and the low delay introduced in the overall operation of the receiver chain.